The Chemical and Organoleptic Characteristics of Beef Meatballs Added With Butterfly Pea Flower Powder (Clitoria ternatea L.) - HARIADI, Hari; MAULANA, Haris; SARI, Dwi Novanda; SARIFUDIN, Ahcmat; KARJADI, Asih Kartasih; AZMI, Chotimatul; SOEDOMO, Prasodjo; MANZIL, Ifa; PURNAMANINGSIH, Ragapadmi; KUSMANA, KUSMANA; AMBARWATI, Alberta Dinar; HIDAYAT, Hidayat; et al. (Food Science and Technology, 2024)
Meatballs are one of the favorite foods in the world. Adding butterfly pea flower powder to meatball products can increase their functional value. This study aimed to determine the effect of the concentration of butterfly pea powder on the chemical and organoleptic characteristics of the meatballs. The research methodology included four treatments and three repetitions. The experimental design used was a completely randomized design (CRD) with four treatments, namely, T0 (control), T1 (0.75 g/300 g butterfly pea flower extract), T2 (1.5 g/300 g butterfly pea flower extract), and T3 (2.25 g/300 g of butterfly pea flower extract). This study shows the highest water content in the T3 formulation of 79.63% and the lowest in the T1 formulation of 63.36%. The highest fat content was in the T3 formulation of 17.11% and the lowest was in the T0 formulation of 16.28%. The highest protein content was in the T3 formulation of 15.25%, and the lowest protein content was in the T0 formulation of 14.66%. This study also showed the antioxidant activity with the intensity of the IC50 value in the moderate category in the T1 formulation of 117.29 mg/L. It showed the active category in the T3 formulation of 87.13 mg/L. The formulation of beef meatballs with the addition of butterfly pea flower powder did not significantly affect the value of protein content, fat content, and antioxidant activity contained therein. Differences in the formulation of beef meatballs with the addition of pea powder significantly affected the quality attributes of aroma, texture, taste, and color in the four treatments.